Culture of hybrid spheroids composed of calcium phosphate materials and mesenchymal stem cells on an oxygen-permeable culture device to predict in vivo bone forming capability. (1st April 2019) - Sato, Tomoya; Anada, Takahisa; Hamai, Ryo; Shiwaku, Yukari; Tsuchiya, Kaori; Sakai, Susumu; Baba, Kazuyoshi; Sasaki, Keiichi; Suzuki, Osamu
Graphical abstract: Abstract: Three-dimensional (3-D) cell culture can better mimic physiological conditions in which cells interact with adjacent cells and the extracellular matrix than monolayer culture. We have developed a 3-D cell culture device, the Oxy chip, which can be used to generate and supply oxygen to cell spheroids to prevent hypoxia. Here, we used the Oxy chip to generate hybrid spheroids comprising calcium phosphate (CaP) particles (hydroxyapatite (HA), β-tricalcium phosphate (β-TCP) or octacalcium phosphate (OCP)) and mesenchymal stem cells (MSCs, C3H10T1/2 cells or D1 cells) that can be used to analyze cell differentiation mechanisms. We showed that the 3-D cell-cell and cell-material interactions and oxygenation offered by the Oxy chip promoted osteoblastic differentiation of MSCs. We also used histomorphometric analysis of hematoxylin and eosin staining, quality analyses by μCT and collagen orientation observation with picrosirius red staining in bone regeneration following implantation of three CaPs in a critical-sized defect in mouse calvaria. The in vivo bone formation capacity of the three tested CaP materials was OCP ≥ β-TCP > HA: the newly formed bone by OCP had a structure relatively close to that of the calvaria intact bone. When MSCs were 3-D cultured with the CaP materials using the Oxy chip, the in vitro osteogenic capacity of these materials was highly similar to trends observed in vivo. The in vitro alkaline phosphatase activity of D1 cells had the highest correlation with in vivo bone volume (R = 0.900). Chemical and FTIR spectroscopic analyses confirmed that differentiation of D1 cells could be associated with amorphous calcium phosphate (ACP) precipitation concomitant with OCP hydrolysis. Taken together, hybrid spheroid cultures using the Oxy chip can be used to screen and predict bone forming potential of bone substitute materials. Statement of significance: An oxygen permeable-culture chip (Oxy chip) can be used to induce formation of cell spheroids by mesenchymal stem cells (MSCs). Use of the Oxy chip avoids hypoxia in the spheroid core and enhances MSC osteoblastic differentiation relative to conventional spheroid culture methods. The present study showed that the Oxy chip mimics the in vivo environment associated with bone formation and can be used to generate hybrid spheroids consisting of calcium phosphates and MSCs that are useful for analyzing cell differentiation mechanisms. Bone formation analysis following implantation of calcium phosphate materials in mouse calvaria defects showed positive correlation with the in vitro results. We propose that hybrid spheroids cultured on the Oxy chip can be used to screen and predict the bone forming potential of bone substitute materials.